(untitled) (Acta Scientiarum. Agronomy, 2019)
The objective of this study was to verify the activity of invertases in Estilosantes under the influence of cultivation systems and nitrogen fertilization in two seasons. The experiment was conducted in the Xaraés area, where Estilosantes was planted according to a 2 x 2 factorial scheme with two cultivation systems (monoculture and mixed pasture) in the absence or presence of fertilization (75 kg of N ha-1). A randomized block design with four replications was used. The neutral cytosol (Inv-N), vacuole acid (Inv-V) and cell wall acid (Inv-CW) invertase activity and reducing sugar contents in the leaves and stems were evaluated and analyzed by a 5% probability F-test. The interaction between cultivation systems and nitrogen fertilization was significant for Inv-N in the leaves in the summer, such that greater activity occurred in response to the mixed pasture system and nitrogen fertilization. Nitrogen increased the activity of the Inv-N in the stem in both periods, increased the activity of Inv-V in the leaf in the summer, and decreased the activity of Inv-CW in the fall. This cultivation system influenced the activity of Inv-N regardless of the period of the year and did not interfere with the activities of the acid invertases. The invertases did not show regular changes in relation to nitrogen fertilization.